Fullerene C70‐Encapsulated Tetrathiafulvalene‐Co Porphyrin Covalent Organic Framework: Driving Multistep Charge Transfer to Boost CO2 Photoreduction - Ying Jiang; Chong Wang; Tianyang Dong; Yupeng Song; Tao Wang; Haibing Che; Hua Sheng; Bo Wu; Chunru Wang (Advanced Science)
Abstract Constructing an efficient charge transfer system can significantly enhance photocatalytic CO2 reduction, yet efficient construction strategies remain to be explored. In this work, fullerene C70 is encapsulated into the tetrathiafulvalene‐Co porphyrin (TTF‐CoTPP) COF to fabricate an efficient photocatalyst C70@COF. Transient absorption (TA) spectra indicate that C70 significantly promotes photogenerated charge separation (0.3 ps), subsequently driving multistep charge transfer within the composite system. This process ultimately yields a long‐lived charge‐separated state, TTF•+‐CoTPP‐C70 •− (>5 ns). Density functional theory (DFT) calculation reveals that the encapsulation of C70 forms a new electron transfer pathway and reduces the energy barrier for *COOH intermediate formation. The C70@COF exhibits a remarkable CO production rate of 4963.24 µmol g h−1, a 1.95‐fold enhancement over the pristine COF. This work highlights the potential of fullerene in boosting photocatalytic CO2 reduction performance and offers a facile strategy to design novel COF‐based photocatalysts.